2014
DOI: 10.1152/ajpendo.00048.2014
|View full text |Cite
|
Sign up to set email alerts
|

Central adiponectin administration reveals new regulatory mechanisms of bone metabolism in mice

Abstract: Adiponectin (APN), the most abundant adipocyte-secreted adipokine, regulates energy homeostasis and exerts well-characterized insulin-sensitizing properties. The peripheral or central effects of APN regulating bone metabolism are beginning to be explored but are still not clearly understood. In the present study, we found that APN-knockout (APN-KO) mice fed a normal diet exhibited decreased trabecular structure and mineralization and increased bone marrow adiposity compared with wild-type (WT) mice. APN intrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
57
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(62 citation statements)
references
References 51 publications
4
57
1
Order By: Relevance
“…Similar to the previously described study, centrally administered adiponectin decreased sympathetic tone and produced increase in fractional volume of trabecular bone in both WT and APN-KO mice. Adiponectin infusion increased the expression of osteoblast markers and decreased the number of osteoclasts [44]. In contrast to the previous study [46], this study suggested that while the local effect of adiponectin on osteoblasts may oppose its central effect, adiponectin's effects on osteoclasts and bone resorption are similar regardless of the site of action.…”
Section: Studies In Adiponectin-knockout Micecontrasting
confidence: 96%
See 3 more Smart Citations
“…Similar to the previously described study, centrally administered adiponectin decreased sympathetic tone and produced increase in fractional volume of trabecular bone in both WT and APN-KO mice. Adiponectin infusion increased the expression of osteoblast markers and decreased the number of osteoclasts [44]. In contrast to the previous study [46], this study suggested that while the local effect of adiponectin on osteoblasts may oppose its central effect, adiponectin's effects on osteoclasts and bone resorption are similar regardless of the site of action.…”
Section: Studies In Adiponectin-knockout Micecontrasting
confidence: 96%
“…Osteoblasts cultured from the APN-KO mice expressed lower levels of RANKL and higher levels of osteoprotegerin (OPG) than WT mice, a change that might explain the lower numbers of osteoclasts and the lower levels of circulating bone resorption markers found in the APN-KO mice. Intracerebroventricular infusion of adiponectin in APN-KO and WT mice was also used to differentiate between the local effect of adiponectin on bone and its centrally mediated activity, as in this model system only negligible amounts of the infused adiponectin reach the circulation [44]. Similar to the previously described study, centrally administered adiponectin decreased sympathetic tone and produced increase in fractional volume of trabecular bone in both WT and APN-KO mice.…”
Section: Studies In Adiponectin-knockout Micementioning
confidence: 90%
See 2 more Smart Citations
“…When there is a combination of impaired bone, muscle, and adipose tissue functions, a new clinical phenotypic entity arises, termed osteosarcopenic obesity, comprising the interrelation and consequent dyshomeostasis between the three tissues [84,85]. Currently, there is a lack of consensus regarding this clinical entity.…”
Section: Osteosarcopenic Obesitymentioning
confidence: 99%